Letter (copy) : Basque Children's Fund - Citrine, Walter, 1887-1983
038-0097-001 24th April, 1939. Mr. C.W. Luker. Forest of Dean Div. Labour Party, Glenville, Whitecroft, Nr. Lydney, Glos. Dear Mr. Luker, BASQUE CHILDRENS FUND. We have received the accompanying letter and cheque drawn to the order of Mr. R.H. Ley, both of which appear to have been forwarded to this office in error. On the other hand, however, the envelope containing these documents was addressed to the National Council of Labour. If it was intended that this donation should have been remittted to the Council's Fund for Basque Children, perhaps you will be good enough to let me have an amended cheque at your convenience. Yours sincerely, Joint Secretary. Encs. 292/946/38/97